Ozone therapy influence in the tissue repair process: A literature review - Néri, Júlia dos Santos Vianna; Lomba, Erielma; Karam, Alexandre Melo; Reis, Silvia Regina de Almeida; Marchionni, Antônio Márcio Teixeira; Medrado, Alena Ribeiro Alves Peixoto (Journal of Oral Diagnosis, 2017)
Introduction: The ozone therapy is a bio-oxidation therapy, based on a gaseous mixture with oxygen and ozone. It can be considered an alternative therapeutic tool the treat- ment of many systemic and locals diseases. It induces acute oxygenation stress and is not deleterious, which allows the restoration of oxidation and reduction balance. Within the therapeutic effects, it has been associated to the improvement metabolism and the peripheral tissue oxygenation. In addition, ozone is an important antimicrobial agent against bacteria, fungi, protozoa and viruses. In Dentistry, the ozone therapy has been used in several clinical situations due to its mechanisms of action. Objectives: The pur- pose of this literature review is to discuss the chemical and physical properties of ozone and its mechanisms of action in tissue repair. Methods: It is a narrative review based on research articles searched in Pubmed and LILACS database, from December 2015 to May 2016. The following descriptors in English: “ozone”, “oxidative stress” and “tissue repair” used. Finally, 36 articles were included in this narrative literature review. Results and Conclusion: The use of ozone as treatment seems to be promising in health areas, including dentistry due to its biological and biochemical properties. However, there is a need for more methodologically adequate studies so it can be safely and efficiently applied.